Learning Community Management in Developing a Culture of Teacher Collaboration in the Learning Process - Wisnurat, Yuyus; Wasliman, Iim (Papanda Publisher, 2025)
This study examines learning community management in developing teacher collaboration culture at SMAN 23 Bandung and SMKN 2 Cimahi using George R. Terry's management framework. A qualitative multiple case study approach was employed, utilizing in-depth interviews with school principals, learning community coordinators, and participating teachers, combined with observation of learning community sessions and document analysis. Data were analyzed through the Miles and Huberman framework, focusing on planning, organizing, actuating, and controlling functions. The findings reveal that effective learning community management requires data-driven planning based on student learning outcomes and teacher needs assessment, flexible organizational structures with rotational leadership roles, active implementation through technology-enhanced collaboration and integrated scheduling, and participatory supervision emphasizing improvement over compliance. Both institutions achieved 100% teacher participation rates and demonstrated significant improvements in collaborative lesson planning and instructional quality. However, cross-subject collaboration remained limited, indicating areas requiring additional intervention. The study contributes to educational management literature by demonstrating the practical applicability of classical management principles within contemporary collaborative learning contexts. The research provides evidence-based strategies for educational administrators seeking to implement sustainable learning communities, particularly in developing country contexts where resource constraints and cultural factors present unique challenges. These findings offer actionable guidance for bridging the implementation gap between educational policy intentions and practical realities in fostering teacher collaboration.